1998
DOI: 10.1046/j.1471-4159.1998.70010397.x
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐State Cerebral Glucose Concentrations and Transport in the Human Brain

Abstract: Understanding the mechanism of brain glucose transport across the blood-brain barrier is of importance to understanding brain energy metabolism. The specific kinetics of glucose transport have been generally described using standard Michaelis-Menten kinetics. These models predict that the steady-state glucose concentration approaches an upper limit in the human brain when the plasma glucose level is well above the Michaelis-Menten constant for half-maximal transport, K~. In experiments where steady-state plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
288
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(320 citation statements)
references
References 58 publications
31
288
0
1
Order By: Relevance
“…More recently Gruetter and coworkers 52 have used 1 H MRS at 4 T to analyze the relationship between plasma and brain steady-state glucose concentration over a very wide range of glucose concentration. In this study the brain glucose concentration was found above normal levels to be in a constant ratio of concentration with plasma glucose.…”
Section: In Vivo Mrs Studies To Test Models Of Glucose Transportmentioning
confidence: 99%
“…More recently Gruetter and coworkers 52 have used 1 H MRS at 4 T to analyze the relationship between plasma and brain steady-state glucose concentration over a very wide range of glucose concentration. In this study the brain glucose concentration was found above normal levels to be in a constant ratio of concentration with plasma glucose.…”
Section: In Vivo Mrs Studies To Test Models Of Glucose Transportmentioning
confidence: 99%
“…Plasma glucose concentrations of <3 mM lead to impaired cognitive function [3,4], and limitations of glycolysis [17,18].…”
Section: Comparison Of In Vitro Glucose Ambient Levels and In Vivo CLmentioning
confidence: 99%
“…S was assumed to be 0.77 ml/g [29]. The mean value of K t =4.05, as collated by Gruetter et al, was used [39].…”
Section: Biochemical Analysesmentioning
confidence: 99%